Determining the Factors Influencing Use of Mobile Marketing by Industrial Firms : An Empirical Investigation of Jordanian Industrial Firms - Eneizan, B. M.; Wahab, Kalsom Abd. (Indian Journal of Computer Science, 2016)
One of the most powerful aspect of marketing that facilitates marketing experiences is mobile marketing (m-marketing).The expeditious advancements in ICT (information & communication technology) and mobile technology have brought about the development of various new services and applications. This creates a substantial need to look into factors that influence use of m-marketing by industrial firms in Jordan. The present study examined three models and theories, Technology Acceptance Model (TAM), Theory of Reasoned Action (TRA) and Unified Theory of Acceptance and Use of Technology (UTAUT). The basis of this study is a survey which was conducted across distinct groups of industries which belong to a range of industrial firms. In all, the survey questionnaires were distributed to 300 respondents to gather the pertinent data. The study found that aspects like the respondents perceived self efficacy and facilitating conditions showed significant and positive effect on adoption of m-marketing by industrial firms. Meanwhile, the aspect perceived quality of service did not show any significant impact on the implementation of m-marketing among industrial firms in Jordan.